Measurement of myocardial fractional flow reserve during coronary angioplasty in infarct-related and non-infarct related coronary artery lesions - (:unkn) unknown (HEALTH MANAGEMENT PUBLICATIONSINC, 2000)
Myocardial fractional flaw reserve (FFRmyo) has been demonstrated to be a useful method for determining the physiologic importance of a given coronary lesion. However, the reliability of the FFRmyo measurement is unknown in infarct-related arteries (IRA). The aim of this study was to measure and correlate the FFRmyo results of 14 consecutive patients who had recent acute myocardial infarction (AMI) (Group 1) with 14 consecutive patients who didn't have AMI (Group 2) before and after percutaneous transluminal coronary angioplasty (PTCA). Quantitative coronary angiography (QCA) and FFRmyo measurements were determined both before and after optimal PTCA for all patients. FFRmyo was measured by use of a 0.014 inch guidewire as the ratio of the pressure distal to the target lesion to the aortic pressure taken during the maximal hyperemia induced by intracoronary adenosine. There were no differences between the two groups related to gender, target artery reference diameter, minimal luminal diameter and percent diameter stenosis of the vessel both before and after PTCA. While FFRmyo results after PTCA were not different between the groups, they were statistically different before PTCA (Group 1: 77.6 +/- 5.1%, Group 2: 63.3 +/- 8.4%; p < 0.001). Although QCA-determined percent diameter stenosis revealed a significant degree of stenosis (66.5 +/- 10.5%) for Group 1, FFRmS a values were higher than 75% (77.6 +/- 5.1%), indicating insignificant stenosis. Thus, it was concluded that FFRmyo measurements before PTCA were significantly different between IRA. and non-IRA and that the method may not be valid far the determination of stenosis significance in IRA.
Keywords: balloon angioplasty; coronary stenosis; myocardial infarction myocardial ischemia; myocardial reperfusion; BLOOD-FLOW; PRESSURE MEASUREMENTS; STENOSIS; VELOCITY; HEMODYNAMICS; ANGIOGRAPHY; VIABILITY; SEVERITY; RECOVERY